The Role of Teaching Factory in Forming Vocational Students’ Work Readiness: A Literature Review - Dyah Ayu Kensasmi Putri; Rina Febriana Hendrawan; Guspri Devi Artanti; Constantinus Rudy Prihantoro; Muhammad Nurtanto (Jurnal Pendidikan Progresif, 2026)
Teaching Factory (TeFa), which integrates an industrial work environment into schools, has been widely implemented in vocational education to bridge the gap between schools and industry. Previous studies have reported TeFa’s ability to enhance students’ work readiness by developing soft skills. The purpose is to synthesize the extent of TeFa implementation and examine its contribution to the development of soft skills that support vocational students’ work readiness. This study used a systematic literature review of 35 articles published between 2022 and 2026. A thematic and comparative synthesis of data was conducted using articles selected based on compliance with inclusion and exclusion criteria. The articles were retrieved from databases and analyzed to identify codes and themes related to TeFa and its impact on students’ work readiness. Literature review revealed a positive relationship between the implementation of TeFa and vocational students’ work readiness. The findings identified 12 soft skills associated with TeFa implementation, including adaptability, communication, teamwork, problem-solving, critical thinking, leadership, flexibility, creativity, initiative, responsibility, entrepreneurship, and innovation. The most frequently reported skills in this literature were adaptability (22%), communication (19%), and teamwork (15%). The findings suggest that these soft skills can be organized into three competency clusters: adaptive, collaborative, and value-creation. Despite the positive impact, challenges remain, including limited industrial partnerships, inadequate facilities, budget constraints, and variations in educator competency. TeFa has been an effective approach for strengthening vocational students’ work readiness by fostering soft skills through authentic learning. Therefore, future research should focus on developing comprehensive implementation and evaluation frameworks to support more systematic, effective, and sustainable implementation of TeFa.   Keywords: teaching factory, evaluation, soft skills, work readiness.